Components, mechanisms and applications of stimuli-responsive polymer gels. (15th August 2022) - Yuan, Zhiang; Ding, Junjie; Zhang, Yu; Huang, Bin; Song, Zhaohui; Meng, Xiangxin; Ma, Xintao; Gong, Xuyang; Huang, Zixu; Ma, Songmei; Xiang, Shidong; Xu, Wenlong
Graphical abstract: Abstract: With the development of the bionics and artificial intelligence, materials that can detect and respond to complex environments will be required. Gels are considered a potential material due to its similarity to biological tissue and its special three-dimensional network structure. In recent years, gels synthesized from stimuli-responsive polymers have excellent detection and response capabilities, expanding the application scope of gels in the fields of biomedicine and mechanical engineering. Gels synthesized from different stimuli-responsive polymers can exhibit various macroscopic feedback phenomena based on different physical/chemical interactions, which exhibit a range of properties far beyond traditional gels. In this review, we first analyze the response mechanism of various responsive gels, and focus on summarizing the response components in various responsive gels. At the same time, we introduce the application status of various response gels, and analyze the advantages of dual and multiple response gels compared with single-response gels in the field of drug delivery, 3D printing and actuators. We hope this review can help readers understand the response mechanism, response components, and application status of gels synthesized from stimuli-responsive polymers, and bring some inspiration for the design of required materials.